Comparative outcomes of thyroid surgery in elderly patients: A retrospective cohort study - Ataş, Hakan; Nasıroğlu İmga, Narin (Journal of Surgery and Medicine, 2020)
Aim: The prevalence of benign and malignant thyroid diseases increases with age. Since the population continues to age, the necessity and feasibility of thyroid surgery in the elderly has become more questionable. The aim of this study is to evaluate thyroid surgery and determine whether thyroidectomy is a safe option in the elderly population, by comparing with younger counterparts. Methods: The data of 471 consecutive patients (370 females, 101 males) with benign or malignant thyroid disorders who underwent thyroid surgery between June 2016 and May 2018 were evaluated retrospectively. The patients were divided into two groups, as younger (age <65) and elderly group (age ≥65). Both groups were compared in terms of indications, post-surgical complications, and histopathological results. All statistical tests were performed using SPSS, version 18.0, software (SPSS Inc., Chicago, IL). Results: Thyroid surgery in the elderly patients showed similarities compared to younger patients in terms of indications and most of the postoperative complications (P>0.05 for each). However, some differences were seen such as increased postoperative hemorrhage and length of hospital stay in favor of the elderly (P=0.035 and P<0.001, respectively).The incidence of malignant disease was found to be slightly higher in the younger group compared to the elderly (42.96% vs. 31.81%, respectively, P=0.095). Surgery-related death was not observed. Conclusion: Our experience confirms that successful results can be achieved with low morbidity in experienced hands if careful and close monitoring of co-morbid conditions is provided in elderly patients.